2015
DOI: 10.1016/j.ajpath.2015.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Jak2-Stat5a/b Signaling Induces Epithelial-to-Mesenchymal Transition and Stem-Like Cell Properties in Prostate Cancer

Abstract: Active Stat5a/b predicts early recurrence and disease-specific death in prostate cancer (PC), which both typically are caused by development of metastatic disease. Herein, we demonstrate that Stat5a/b induces epithelial-to-mesenchymal transition (EMT) of PC cells, as shown by Stat5a/b regulation of EMT marker expression (Twist1, E-cadherin, N-cadherin, vimentin, and fibronectin) in PC cell lines, xenograft tumors in vivo, and patient-derived PCs ex vivo using organ explant cultures. Jak2-Stat5a/b signaling ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 89 publications
3
67
0
Order By: Relevance
“…Our data revealed STAT5A as a target of miR-4521 and miR-339-5p, both of which also interact with hg19_circ_0005033. Particularly, STAT5A induces stem-like cell properties and the epithelial-to-mesenchymal transition in prostate cancer [45]. hg19_circ_0005033 may upregulate STAT5A to promote the phenotype of LSCC stem cells by binding miRNAs targeting STAT5A.…”
Section: Discussionmentioning
confidence: 99%
“…Our data revealed STAT5A as a target of miR-4521 and miR-339-5p, both of which also interact with hg19_circ_0005033. Particularly, STAT5A induces stem-like cell properties and the epithelial-to-mesenchymal transition in prostate cancer [45]. hg19_circ_0005033 may upregulate STAT5A to promote the phenotype of LSCC stem cells by binding miRNAs targeting STAT5A.…”
Section: Discussionmentioning
confidence: 99%
“…Shrimp Stat is similar to mammalian Stat5a/b. In mammals, Jak2 and 34445 regulate Stat5a/b and the inhibitors are Socs246, TC-PTP47 and PTP1B48. The inhibitor SOCS2 has also been cloned in shrimp38.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer stem cells can also be derived from reprograming of differentiated cells via epithelial-mesenchymal transition (EMT), in which epithelial cells lose their polarity and cell–cell adhesion and gain migratory and invasive properties of mesenchymal cells (Kong et al, 2010; Talati et al, 2015; Lee et al, 2016). Kong et al (2010) reported that overexpression of platelet-derived growth factor D (PDGFD) resulted in the loss of epithelial markers and increasing mesenchymal markers in prostate cancer cells.…”
Section: The Origin Of Pcscsmentioning
confidence: 99%
“…5-Aza treated prostate cancer cells showed enhanced CD133 + CD44 + phenotype and prostasphere formation ability, and elevated expression of stem cell-related transcription factors KLF4 and Sox2 (Lee et al, 2016). Activation of Jak2-Stat5a/b signaling promotes metastasis by inducing EMT and stem cell properties in prostate cancer cells, as shown by sphere formation and expression of CSC markers BMI-1, CD44, and Sox2 (Talati et al, 2015). Recently, there is an emerging concept that EMT represents a spectrum of differentiation status ranging from fully epithelial to fully mesenchymal status (Nieto et al, 2016).…”
Section: The Origin Of Pcscsmentioning
confidence: 99%